Characteristics Predicting Tuberculosis Risk under Tumor Necrosis Factor-alpha Inhibitors: Report from a Large Multicenter Cohort with High Background Prevalence - DİRESKENELİ, RAFİ HANER (J RHEUMATOL PUBL CO, 2016)
Objective. Screening strategies for latent tuberculosis (TB) before starting tumor necrosis factor (TNF)-alpha inhibitors have decreased the prevalence of TB among patients who are treated with these agents. However, despite vigilant screening, TB continues to be an important problem, especially in parts of the world with a high background TB prevalence. The aim of this study was to determine the factors related to TB among a large multicenter cohort of patients who were treated with anti-TNF. Methods. Fifteen rheumatology centers participated in this study. Among the 10,434 patients who were treated with anti-TNF between September 2002 and September 2012, 73 (0.69%) had developed TB. We described the demographic features and disease characteristics of these 73 patients and compared them to 7695 patients who were treated with anti-TNF, did not develop TB, and had complete data available. Results. Among the 73 patients diagnosed with TB (39 men, 34 women, mean age 43.6 +/- 13 yrs), the most frequent diagnoses were ankylosing spondylitis (n = 38) and rheumatoid arthritis (n = 25). More than half of the patients had extrapulmonary TB (39/73, 53%). Six patients died (8.2%). In the logistic regression model, types of anti-TNF drugs [infliximab (IFX), OR 3.4, 95% CI 1.88-6.10, p = 0.001] and insufficient and irregular isoniazid use (<9 mos; OR 3.15, 95% CI 1.43-6.9, p = 0.004) were independent predictors of TB development. Conclusion. Our results suggest that TB is an important complication of anti-TNF therapies in Turkey. TB chemoprophylaxis less than 9 months and the use of IFX therapy were independent risk factors for TB development.
Keywords: TUMOR NECROSIS FACTOR-A INHIBITORS; TUBERCULOSIS REACTIVATION; ISONIAZID; RHEUMATOID-ARTHRITIS; FACTOR ANTAGONISTS; THERAPY; TNF; MORTALITY; INFECTIONS; TERM